Feeding ecology of the Molé Trachelyopterus galeatus Linnaeus, 1766 (Siluriformes, Auchenipteridae) in the lower course of the São José and Santo Antônio Rivers (Chapada Diamantina, Bahia) - Santos, Alexandre Clistenes Alcântara (SITIENTIBUS série Ciências Biológicas, 2005)
The São José and Santo Antônio Rivers are representative affluents of the Paraguaçu River, although they have demonstrated different physiographic conditions and differ in their degrees of anthropogenic disturbance. In this work, the feeding ecology of Trachelyopterus galeatus was described, as well as the possible effects of the alterations previously caused by former diamond mining on the São José bed and margins. Feeding was analyzed through the Frequency of Occurrence and by the Volumetric method combined in an Alimentary Index. The niche width was then calculated. The results indicate a lesser contribution of allochthonous items in the São José River. This may be due to the effects of deforestation along its margins, which would influence species that are dependent upon those resources. Among the parameters analyzed, the lesser proportion of allochthonous items in the diet of fish from the São José River was marked and can be considered an indirect result of previous mining activity in the area.